MENGOPTIMALKAN KESEJAHTERAAN SUMBERDAYA MANUSIA (SDM) DI KELURAHAN BUMI AYU - Sri Endang Kornita; Aisya Zesi Azani; Andini Putri Utami; Aninisa Damayanti; Dwi Zahra Ramadhani; Harum Fatanah; Pitriyani Pitriyani; Rifki Wanda Gemala; Riri Ulfa Hariyani; Sabina Azhar; Syahrul Rizal (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The Field Work Lecture was held in the Bumi Ayu Village, Dumai Selatan District, Dumai City, Riau for 40 days from 10 July to 18 August 2023. The Bumi Ayu Village was chosen as the destination to carry out the KKN. The village's abundant potential is one of the goals to be able to improve the quality of Human Resources (HR), as well as cultivate and also develop potential in the village. Activities are carried out with a process of socialization and observation to find out and develop the potential of existing villages. The Real Work Lecture work program is carried out sequentially, starting with discussions between the Field Work Lecture group and village officials and the local community, especially with the people concerned. Real Work Lectures are carried out in stages starting from planning, implementation and evaluation at the end of each activity carried out. The results achieved from the Real Work Lecture program which was carried out as a whole were increasing human resources, which were useful for developing the potential of local villages. In the environmental sector, greening activities and processing organic waste into liquid soap received a positive response and active participation from the people of the Bumi Ayu Village, Dumai Selatan District, Dumai City, Riau.